EKSEKUSI BARANG SITAAN TINDAK PIDANA KORUPSI YANG TIDAK SESUAI DENGAN NILAI KERUGIAN NEGARA PADA WILAYAH HUKUM KEJAKSAAN TINGGI SUMATERA BARAT - Irawadi, Nanang (LPPM Universitas Ekasakti Padang, 2019)
The state losses on corruption can be preceded by the seizure formulated in Article 1 number 16 of the Criminal Procedure Code. Objects that do not match the amount to the value of the State losses become an issue on the execution of the judge's verdict. The specification in this research is descriptive analytical. The results of research indicate that the implementation of additional criminal state losses relating to objects or convicted goods that have been confiscated at the stage of investigation and prosecution is to the confiscated body status dirobah into objects used to pay additional penal redress state losses. If sufficient confiscated goods will be immediately taken over by the State, if less than the amount of criminal liabilities of the State shall be added by the convict with his other property. If there is an excess it will be refunded or set its status with the judge's determination. the constraint faced by the Prosecutor in executing the execution associated with confiscated objects is the unclear amount of the wealth of the convicted person. There are those who intend to pay but can not afford to pay at once. The existence of the property of the convict has moved into a domicile but is not known to exist. The existence of a conspiracy between the convicted person and the examiner team of the convicted property. As a result of manipulation of data stating that the convicted person does not have enough wealth to pay the replacement money.